Gluten-free cookies enriched with orange residue flour - Miranda, Matheus Santos (2021)
This study aimed to develop cookie-type cookies from the use of orange residue flour as a partial replacement for rice flour (ORF0%, ORF10%, ORF20%). Microbiological, physicochemical analyzes (pH, aW and instrumental color) and sensory analysis were performed using the hedonic scale, purchase attitude and ideal scale, evaluating flavor, crispness and aftertaste. Microbiological analyzes indicated absence for coliforms at 45°C, mesophilic aerobic bacteria and Salmonella sp. Regarding the results of instrumental color, there was no significant difference in the parameter b* for the three samples, however there was a significant difference for the intensities of L* and a*. The aW results of the tested samples did not differ significantly from each other, however, the pH showed a reduction according to the increase in the orange residue flour content. As for the sensory analysis, no significant differences were observed (p<0.05) for the attributes color, aroma, texture, acidity and global impression between samples containing 10 and 0% of orange residue flour. It was observed that the crispness and aftertaste of the samples with ORF10% and ORF0% were similar and ideal according to the test, which implies that the replacement of ORF10% was quite satisfactory and with sensory characteristics like those of cookies made with flour of rice. Therefore, the orange residue flour is a viable alternative to produce this model of cookies, knowing that this is a little used residue to produce cookies.